How to read Bible stories and myths in art : decoding the old masters, from Giotto to Goya - Rynck, Patrick de, 1963- (New York : Harry N. Abrams, 2008)
"In How to Read Bible Stories and Myths in Art: Decoding the Old Masters from Giotto to Goya, Patrick De Rynck examines over two hundred of these works. The result is a book that explores the roots of Western civilization from three different angles: It introduces or re-introduces the reader to the best-known stories from the Bible and mythology; it presents a selection of exquisite masterpieces by some of the world's greatest painters; and it shows the reader how these painters interpreted these famous scenes."--Jacket.
Abraham -- Achilles -- Adam and Eve -- Anna and Joachim -- Antiope -- Apollo -- Arachne -- Babel -- Bacchus and Ariadne -- Balaam -- Belshazzar -- cambyses -- Cephalus and Procris -- Ceres -- Jesus Christ -- Cimon and Pero -- Constantine -- Danae -- Daniel -- David -- Diana -- Dido -- Erichthonius -- Esther -- Europa -- Ganymede -- Gyge and Candaules -- Hannibal -- Hercules -- Hermaphroditus -- Horatii -- Icarus -- Io -- Jacob -- Jeremiah -- Job -- John the Baptist -- Joseph, son of Jacob -- Judith -- Julius Civilis -- Leda -- Lot -- Lucretia -- Mary, the Holy Virgin -- Mercury -- Midas -- Moses -- Mucius Scaevola -- Narcissus -- Noah -- Orpheus -- Pan and Syrinx -- Paris (by Cranach the Elder) -- Paul -- Penelope -- Perseus and Andromeda -- Peter -- Phaeton -- Philemon and Baucis -- Priapus -- Prometheus -- Psyche -- Rebecca -- Sabines -- Solomon -- Samson -- Saturn -- Selene and Endymion -- Seneca -- Susanna -- Tobias -- Troy -- Venus -- Vertumnus and Pomona.
Includes bibliographical references (pages 347-348) and indexes.
Keywords: Mythology, Classical, in art; Bible -- Illustrations; Painting, European